Do employee-friendly firms invest more efficiently? Evidence from labor investment efficiency - Cao, Zhangfan; Rees, William (Journal of Corporate Finance, 2020)
We investigate the impact of employee treatment on labor investment efficiency. We provide evidence that employee-friendly treatment is significantly associated with lower deviations of labor investment from the level justified by economic fundamentals, i.e., higher labor investment efficiency. The effect of employee treatment on labor investment efficiency is stronger for firms that are human-capital-intensive, with more skilled labor and knowledge capital, and those that face higher product market competition. Using the 2008–2009 financial crisis as an external shock and applying the difference-in-difference method, we also show that employee-friendly firms have higher labor investment efficiency in the post-financial crisis period, but experience more inefficient labor investments during the crisis. Our results are robust to placebo tests, selection bias, propensity score matching, alternative explanations, alternative proxies for both employee treatment and labor investment efficiency as well as the adjustment for using residuals as dependent variables, additional control variables, and various approaches in addressing endogeneity issues.